Strategi Pengembangan Agrowisata Durian Sinapeul dengan Pendekatan Interpretative Structural Modelling (ISM) dalam Perspektif Ekonomi Islam - Eni Nuraeni Ruriawati (Jurnal Maps (Manajemen Perbankan Syariah), 2020)
One of the potential areas as an agro-tourism area in Majalengka Regency is the Sinapeul durian agro-tourism area in Ujungberung Village, Sindangwangi District. However, the Sinapeul durian agro-tourism area has not been running optimally, this is thought to be caused by several factors, namely the absence of a strategy and policy on the management and development of the agro-tourism area. In addition, the cooperation agreement that occurs between the village government and smallholders is not yet clear. The purpose of this study was to analyze the strategy for the development of the durian agro-tourism area and to analyze the contract applied between the village government and the tenant farmers. The research method used is a qualitative method with the Interpretative Structural Modeling (ISM) approach. Interpretative Structural Modeling (ISM) is a well-established methodology for identifying relationships between specific variables that define a problem or issue. Based on the results of research that has been conducted by researchers, there are seven elements that become indicators of agro-tourism area development strategies with the main strategies, namely agro-tourism development innovation, institutional support, promotion and marketing (level 1), strengthening regulations and policies, and investors (level 2), quality development. Human resources and community participation with the village (level 3). In Islam, there are several contract options in agricultural management such as Muzara Mukabarah and Musaqah. A cooperative agreement for agricultural production that is suitable for managing durian crops between land owners and smallholders is to apply the Musaqah contract.